Pathophysiology of axial spondyloarthritis: Consensus and controversies. (13th March 2018) - de Koning, Anoek; Schoones, Jan W.; van der Heijde, Desiree; van Gaalen, Floris A.
Abstract: Background: Axial spondyloarthritis (axSpA) is a common inflammatory arthritis of the sacroiliac joints and the spine. The best‐known and most studied form of axSpA is ankylosing spondylitis. Design: In this review, we provide a brief overview of the pathophysiology of axSpA. In addition, we performed a quantitative text analysis of reviews on the pathogenesis of axSpA published in the last 10 years to establish the current consensus in various fields of research into the pathogenesis of axSpA. Results: There appears to be broad consensus on genetic risk factors and the involvement of the immune system in the initiation phase of the disease although little consensus was found on which specific immune cells drive disease. Moreover, despite relatively little data available, alterations in the microbiome are commonly thought to be involved in disease. Abnormal bone formation is the most prominent pathogenic factor thought to be involved in disease progression. Conclusion: So, although the pathophysiology of axSpA remains incompletely understood, the progress in recent years in several fields of research in axSpA including genetics, diagnosis, imaging and therapeutics, hold great promise for the future.